Flyback Topology TEM Bipolar Pulse Transmitter - Guo-fu Wang; Yong-shou Yang; Jin-cai Ye (Institute of Advanced Engineering and Science, 2013)
In the fields of transient electromagnetic (TEM) geophysical exploration, it is necessary to create a bipolar pulse current source with decline edge of high linearity, short turn-off time and high stability. In order to improve detection equipment’s practicality, it’s urgently needed to miniaturize and improve the reliability of the detection equipment. In this paper, a clamp and prompt drop bipolar pulse current circuit based on Flyback topology is represented, which can accelerate the decline of load current by clamping the coil load with fixed high voltage in the period of current declining. Also, because of this circuit’s low power consumption and significantly improvement of the transmitter’s energy utilization, chassis’s cooling equipment can be greatly reduced and it’s easier to miniaturize the transmitter. To start with, the principle of this circuit is represented. Then, the method is given to select the optimal values of circuit’s components. Finally, the results of simulation proves the proposed circuit meeting the requirements much better than those reported, with shorter turn-off time, higher linearity, less energy consumption. In general, this circuit has been successfully applied to a new type of detection equipment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3250